2004
DOI: 10.1023/b:jmsm.0000036276.32211.31
|View full text |Cite
|
Sign up to set email alerts
|

Development of a  -type Ti–12Mo–5Ta alloy for biomedical applications: cytocompatibility and metallurgical aspects

Abstract: Ti-based biocompatible alloys are especially used for replacing failed hard tissue. Some of the most actively investigated materials for medical implants are the beta-Ti alloys, as they have a low elastic modulus (to inhibit bone resorption). They are alloyed with elements such as Nb, Ta, Zr, Mo, and Fe. We have prepared a new beta-Ti alloy that combines Ti with the non-toxic elements Ta and Mo using a vacuum arc-melting furnace and then annealed at 950 degrees C for one hour. The alloy was finally quenched in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 11 publications
1
31
0
7
Order By: Relevance
“…Moreover, alloying titanium with Mo β-stabilizers improves the corrosion resistance [4][5][6][7][8][9][10], in addition to adequate mechanical compatibility and good cytocompatibility [11][12][13][14][15][16] despite one controversial report [17]. Unfortunately, titanium and molybdenum are difficult to alloy through a conventional melting-casting process due to the big difference in melting point and specific gravity between the two metals.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, alloying titanium with Mo β-stabilizers improves the corrosion resistance [4][5][6][7][8][9][10], in addition to adequate mechanical compatibility and good cytocompatibility [11][12][13][14][15][16] despite one controversial report [17]. Unfortunately, titanium and molybdenum are difficult to alloy through a conventional melting-casting process due to the big difference in melting point and specific gravity between the two metals.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Mo is less toxic than Al and V [1]. Many studies have demonstrated the excellent mechanical compatibility and good cytocompatibility of Ti alloys containing Mo, such as Ti-Mo, Ti-Mo-Ta, and Ti-Mo-Zr-Fe [12][13][14][15][16][17]. Karthega et al [18] reported that Ti-15Mo exhibits corrosion resistance similar to that of TNTZ in Hank's solution.…”
Section: Possible Alloy Systemmentioning
confidence: 99%
“…Entre os materiais metálicos convencionais para tal emprego podem ser citados o aço inoxidável ASTM F138, a liga à base de Co-Cr-Mo, e a liga Ti-6Al-4V [2][3][4][5][6][7][8][9][10], sendo este última a mais apropriada para implantes femorais devido à sua alta resistência mecânica, menor módulo de elasticidade e excelente resistência à corrosão [6,7,9,10]. No entanto, nos últimos anos a literatura vem registrando diversos estudos sobre a toxidade dos elementos de liga e a reabsorção óssea como fatores que causam a falha de implantes [7,[9][10][11][12][13][14][15]. Essas preocupações têm estimulado o estudo de novas ligas de titânio que apresentem elementos biocompatíveis e possuam baixos módulos de elasticidade a fim de minimizar a reabsorção óssea, além de oferecer uma elevada resistência à corrosão, uma vez que tais materiais serão usados em meio fisiológico, o qual é bastante agressivo aos metais presentes na composição da liga [3,16].…”
Section: Introductionunclassified